2022
DOI: 10.1186/s12913-022-08449-6
|View full text |Cite
|
Sign up to set email alerts
|

Maternal and child health data quality in health care facilities at the Cape Coast Metropolis, Ghana

Abstract: Background The demand for quality maternal and child health (MCH) data is critical for tracking progress towards attainment of the Sustainable Development Goal 3. However, MCH cannot be adequately monitored where health data are inaccurate, incomplete, untimely, or inconsistent. Thus, this study assessed the level of MCH data quality. Method A facility-based cross-sectional study design was adopted, including a review of MCH service records. It was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 28 publications
1
5
1
Order By: Relevance
“…However, according to the Ghana Health Services report, the fertility rate within the metropolis was 2.2, and the general fertility rate of 59.2 births per 1000 women aged between 15 and 49 years. 30 , 31 Also, although a sufficiently big sample size was used in this study, it is not large enough to conclude for all persons in diverse geographical locations. Therefore, to generalize the findings of this study, it is recommended that larger sample sizes in randomized control trials may be needed.…”
Section: Discussionmentioning
confidence: 99%
“…However, according to the Ghana Health Services report, the fertility rate within the metropolis was 2.2, and the general fertility rate of 59.2 births per 1000 women aged between 15 and 49 years. 30 , 31 Also, although a sufficiently big sample size was used in this study, it is not large enough to conclude for all persons in diverse geographical locations. Therefore, to generalize the findings of this study, it is recommended that larger sample sizes in randomized control trials may be needed.…”
Section: Discussionmentioning
confidence: 99%
“…The introduction of new data quality review interventions, including the establishment of data management committees, the rollout of DHIS2 at the facility level, and relevant knowledge transfer and data monitoring activities in the reference year might also have contributed to inconsistencies in reporting between the reference year and the previous three fiscal years combined. Although the studies assessing consistency over time are limited, few studies in other countries also reported some data quality issue while analyzing trend over the years [ 39 , 40 ]. Differences in values are obvious over period of time; however, if the differences are so large, it usually suggests data quality issue for further scrutiny.…”
Section: Discussionmentioning
confidence: 99%
“…These findings are better while comparing the result with other similar studies assessing outliers [ 42 ]. In contrast, no districts had reported ≥5% monthly values with moderate or extreme outliers in a study conducted in Ruwanda [ 43 ] and Ghana [ 40 ].…”
Section: Discussionmentioning
confidence: 99%
“…Three data collation sheets were used to collect the data on completeness, accuracy, and timeliness in all 23 health facilities over a retrospective 34-month starting from March 2020 to December 2022. These reviews were based on previous studies (5,6,11,15,23,25). The first collation sheet examined the completeness of COVID-19 data in the DHIMS-2 to see whether all data elements were filled.…”
Section: Dhims-2 and Registers Reviewmentioning
confidence: 99%
“…The directorate was automatically hooked onto the DHIMS-2 and started recording high COVID-19 cases after the first case was registered in March 2020, the same month the country recorded its first incident (21). Data documentation and reporting of COVID-19 diseases then took center stage, although numerous studies have shown that data from Ghanaian health facilities are of poor quality in terms of accuracy and timeliness (18,22,23). This highlights the need to assess COVID-19 data quality using the three dimensions of data quality at different levels of the healthcare system.…”
Section: Introductionmentioning
confidence: 99%